New evidence of CO2 soil degassing anomalies on Piton de la Fournaise volcano and the link with volcano tectonic structures. (31st December 2015) - Liuzzo, M.; Di Muro, A.; Giudice, G.; Michon, L.; Ferrazzini, V.; Gurrieri, S.
Abstract: Piton de la Fournaise (PdF) is recognized as one of the world's most active volcanoes in terms of eruptive frequency and the substantial quantity of lava produced. Yet with the sole exception of rather modest intracrateric fumarole activity, this seems to be in contrast with an apparent absence of any type of natural fluid emission during periods of quiescence. Measurement campaigns were undertaken during a long‐lasting quiescent period (2012–2014) and just after a short‐lived summit eruption (June 2014) in order to identify potential degassing areas in relation to the main structural features of the volcano (e.g., rift zones) with the aim of developing a broader understanding of the geometry of the plumbing and degassing system. In order to assess the possible existence of anomalous soil CO2 flux, 513 measurements were taken along transects roughly orthogonal to the known tectonic lineaments crossing PdF edifice. In addition, 53 samples of gas for C isotope analysis were taken at measurement points that showed a relatively high CO2 concentration in the soil. CO2 flux values range from 10 to 1300 g m −2 d −1 while δ 13 C are between −26.6 and −8‰. The results of our investigation clearly indicate that there is a strong spatial correlation between the anomalous high values of diffusive soil emissions and the main rift zones cutting the PdF massif and, moreover, that generally high soil CO2 fluxes show a δ 13 C signature clearly related to a magmatic origin. Key Points: CO2 soil degassing anomalies at Piton de la Fournaise δ 13 C magmatic signature Close link between anomalous CO2 degassing and the main seismotectonic structures